Academic transition from high school to an undergraduate medical program using active methodologies within an integrated curriculum: Qualitative research - Alexandre Ferreira da Silva; Enzo Sá Pantoja da Silva; Daniel Figueiredo Alves da Silva; Selma Kazumi da Trindade Noguchi; Juarez Antônio Simões Quaresma (Educación Médica, 2025)
Introduction: When transitioning from high school to an undergraduate medical program that uses active teaching methodologies, students often encounter clear obstacles in their first semester, such as breaking down disciplinary barriers, adapting to the dynamics of different curricular components, adjusting to an evaluation process that is different from what they are used to, as well as a lack of understanding of the program's pedagogical proposal. This study aims to understand the challenges faced by medical undergraduate students in their first semester, specifically in relation to the use of active teaching methodologies within an integrated curriculum. Material and methods: A qualitative study was conducted through interviews with 15 students from a private medical school who started in the first semester of 2018. The data were categorized and subjected to discourse analysis. Results: The interviewees reported difficulties in understanding the educational proposal. Although they viewed the experience of adapting to the course's methodology positively, they found it challenging. They reported that there was insufficient explanation about the evaluation processes and proposed that clearer educational objectives be established for the students. Conclusion: The need for a more comprehensive explanation of the pedagogical project and its teaching strategies, the importance of valuing practical training in health services, and the clarification of evaluation processes and educational objectives were highlighted by the interviewed students as key pillars for a successful transition from high school to medical education. Resumen: Introducción: La transición del bachillerato a un programa de medicina de pregrado que utiliza metodologías activas de enseñanza suele representar desafíos claros en el primer semestre. Estos incluyen romper barreras disciplinarias, adaptarse a dinámicas curriculares diferentes, enfrentarse a procesos de evaluación desconocidos y comprender la propuesta pedagógica del programa. Este estudio busca comprender los desafíos enfrentados por los estudiantes de medicina durante su primer semestre, específicamente en relación con el uso de metodologías activas en un currículo integrado. Material y metodos: Se realizó un estudio cualitativo mediante entrevistas con 15 estudiantes de una escuela de medicina privada que iniciaron el curso en el primer semestre de 2018. Los datos se categorizaron y analizaron a través de análisis de discurso. Resultados: Los entrevistados reportaron dificultades para entender la propuesta educativa. Aunque perciben positivamente la experiencia de adaptación a la metodología del curso, encontraron obstáculos significativos, como la falta de explicaciones claras sobre los procesos de evaluación. Propusieron la necesidad de establecer objetivos educativos más claros. Conclusión: Se destaca la necesidad de una explicación más completa del proyecto pedagógico y sus estrategias de enseñanza, la importancia de valorar la formación práctica en los servicios de salud y la clarificación de los procesos de evaluación y los objetivos educativos como pilares clave para una transición exitosa del bachillerato a la educación médica.